Integration of Sustainability targets in Executive remuneration and Corporate Sustainability Performance - Evidence from the European Union and the United Kingdom - NGUYEN, THI THUC HIEN (2020)
This study investigates the impact of the integration of sustainability criteria in executive remuneration on corporate sustainability performance (CSP). Drawing upon three theories, namely Expectancy theory, Reinforcement theory and Stakeholder-agency theory, the study proposes that the integration of sustainability targets in executive remuneration has a positive effect on enhancing CSP. In addition, based on the three aforementioned theories, it is also proposed that three corporate governance mechanisms which are (1) the existence of sustainability committee, (2) the existence of sustainability report and (3) the use of external assurance service for sustainability report of the firm have positive moderating impacts on the relationship between sustainability-related executive remuneration and CSP. The paper tests the pooled OLS models on a cross-country sample comprising 279 firms from 19 EU countries and the UK under the period from 2014 to 2018. The results suggest that there is a significant positive impact of sustainability-related executive remuneration and CSP. Furthermore, in contradiction to initial expectation, there is no significant statistical evidence for the moderating impact of sustainability committee. Moreover, the results reveal that the moderating effects of sustainability report and external assurance for sustainability report are significantly negative. By synthesizing these results, previous literature and insights about the context of the EU and the UK, the study suggests that regulators and practitioners promote the integration of sustainability targets in executive remuneration to improve CSP and review the quality of sustainability reporting systems, so that these systems would be able to support the improvement of CSP better. This study has implications for both regulators and practitioners in designing strategic plans for improving CSP.